A simple and efficient hydrogen production-storage hybrid system (Co/TiO2) for synchronized hydrogen photogeneration with uptake. Issue 19 (26th April 2017) - Yang, Yurong; Gao, Peng; Wang, Ying; Sha, Linna; Ren, Xiaochen; Zhang, Jianjiao; Yang, Piaoping; Wu, Tingting; Chen, Yujin; Li, Xiaobo
Abstract : A Co/TiO2 catalyst system efficiently synchronizes hydrogen photogeneration and storage in water at room temperature. Abstract : The production and storage of hydrogen are the two most critical challenges for hydrogen energy development. In addition, converting H2 from the as-obtained gas state to a stable storage state consumes excess energy and increases the practical cost of hydrogen fuel. Accordingly, we now present a simple hybrid material system (Co/TiO2 ) that efficiently synchronizes hydrogen photogeneration in water with its room-temperature storage. In the composite, through a series of carefully controlled experiments, ultrathin Co shells composed of 1, 2, 4, and 9 atom layers have been fabricated on TiO2 photocatalysts. Before saturation of hydrogen on metal Co, the hydrogen storage efficiency is close to 100%, meaning that nearly all hydrogen generated by photocatalytic water splitting is conserved. This work provides a new approach to combined structure-function design technology in the hydrogen energy field.